Product differentiation and cost pass-through: industry-wide versus firm-specific cost shocks - Thomas Bittmann; Jens-Peter Loy; Sven Anders (Australian Journal of Agricultural and Resource Economics, 2020)
This paper investigates the impact of product differentiation on firm-specific and industry-wide cost pass-through in grocery retailing. We use attribute distance measures to model product differentiation based on a unique set of retail scanner data for ready-to-eat soup products in the Canadian market. Results from a panel error correction model suggest that product differentiation explains a significant share of the variation in the rate of cost pass-through across products. More differentiated products are associated with lower rates of cost pass-through of industry-wide and higher pass-through of firm-specific costs shocks. The findings validate an oligopolistic model of product differentiation, where firms use differentiation as a non-price competitive factor in strategic pricing decisions.
Keywords: 330; cost pass-through; non-price competition; product differentiation; industry-wide costs; firm-specific costs; food retail markets; ready-to-eat soups; Canada